PFM.60 Down's Syndrome Screening and counselling: the unseen workload of a Fetal Medicine Midwife. (9th June 2014) - Russell, H; Clegg, I; Brown, S; Tydeman, G
Abstract : Introduction: 1 st trimester Down's syndrome screening has been offered to all antenatal women since 2011 and our unit has made changes to improve the delivery of this service locally. FASP recommends that results should be given when support can be provided and when further options can be discussed . As such all high risk results are now explained by a Specialist Fetal Medicine midwife whereby immediate counselling can be given. We present our 2012 audit including the communication of results to the patients and the decision-making process to a diagnostic test. Method: All cases of increased risk results from Down's syndrome screening in 2012 were reviewed. Data was collated from the annual FM audit. Results: 3856 women in 2012 booked their pregnancy in Fife and of these, 2038 accepted screening (19 were twin pregnancies). There were 57 high risk results, giving a screen positive rate of 2.8%. Our 2 FM specialist midwives made an average of 2 telephone calls per woman. 42 women were counselled by telephone only, 8 women had face-to-face counselling and 7 women had both. There was no significant difference in the uptake of diagnostic testing in these 3 groups. 30/57 women chose to have a diagnostic test and the uptake was directly related to risk result. 5 of these confirmed Down's syndrome and our false positive rate was therefore 2.36%. There were 7 other cases - 3 with high risk results declined diagnostic test, 3 declined screening and 1 late-booker outwith the screening window. No women with a low risk screening result had a baby with Down's syndrome. Discussion: Down's syndrome screening in Fife therefore meets the national screening targets, but this audit highlights the work that FM specialist midwives perform when providing counselling for women after a high risk screening result, PRIOR to attending a FM appointment. This work is often unseen by others as done out with a clinic attendance. References: http://www.screening.nhs.uk/fetalanomaly-scotland http://www.healthscotland.com/topics/health/screening/pregnancynewborn.aspx